2017
DOI: 10.1039/c7ra02983g
|View full text |Cite
|
Sign up to set email alerts
|

The effect of acid treatment on the active sites and reaction intermediates of the low-cost TS-1 in propylene epoxidation

Abstract: This study investigated the roles of the different titanium species of low-cost TS-1 in propylene epoxidation and the influence of acid treatments. The low-cost TS-1 zeolites with different titanium species were synthesized using the hydrothermal method and characterized by ultraviolet (UV)-Raman, X-Ray Diffraction (XRD), ultraviolet visible diffuse reflectance spectroscopy (UV-Vis), N 2 physical absorption and NH 3 temperature programmed desorption (NH 3 -TPD) techniques. The roles of the different titanium s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 23 publications
1
20
0
Order By: Relevance
“…Typically, the framework titanium is the active site for epoxide production during epoxidation reactions, whereas the extra-framework titanium species are responsible for secondary and often unwanted reactions 8 . The extra-framework titanium species include anatase and rutile-type titanium dioxide (TiO2) and amorphous titanium species, which will decompose H2O2 and lead to side reactions, such as hydrolysis and ring opening of the epoxide [9][10][11] . The traditional synthesis method of TS-1 inevitably produces extra-framework titanium, particularly when synthesizing TS-1 with low silicon to titanium ratios [12][13][14] .…”
Section: Introductionmentioning
confidence: 99%
“…Typically, the framework titanium is the active site for epoxide production during epoxidation reactions, whereas the extra-framework titanium species are responsible for secondary and often unwanted reactions 8 . The extra-framework titanium species include anatase and rutile-type titanium dioxide (TiO2) and amorphous titanium species, which will decompose H2O2 and lead to side reactions, such as hydrolysis and ring opening of the epoxide [9][10][11] . The traditional synthesis method of TS-1 inevitably produces extra-framework titanium, particularly when synthesizing TS-1 with low silicon to titanium ratios [12][13][14] .…”
Section: Introductionmentioning
confidence: 99%
“…a novel method to nely tune the acidity of H-beta zeolites. It has been found that dealumination of beta zeolites by steaming, 17 leaching with mineral acids such as HCl, 18 and treatments with chemicals such as ammonium hexauorosilicate, 19 and organic acids 20,21 are effective for this purpose. Among these approaches, acid leaching is considered to be the most feasible route from the point of view of environmental protection and industrial application, but the negative effects of dealumination by acid leaching are structural changes in zeolite crystals and uncontrollable loss of framework aluminum atoms that decreases active sites.…”
mentioning
confidence: 99%
“…The adsorption peak at 270 nm (amorphous Ti species) and 330 nm were appeared when the (NH 4 ) 2 CO 3 /SiO 2 molar ratio was 0.3. The amorphous Ti species and anatase TiO 2 on the surface of s‐TS‐1(0.3) zeolite can be easily washed away by 1 mol/L muriatic acid before calcination (Figure (C) lines e‐f). But the anatase TiO 2 on the surface of conventional TS‐1 zeolite just can be washed away by 3 mol/L muriatic acid (Figure (C) lines a‐d).…”
Section: Resultsmentioning
confidence: 87%
“…The Si/Ti ratio of s‐TS‐1(0.3) is 31.12, after washed with 1 mol/L muriatic acid the Si/Ti ratio of s‐TS‐1(0.3) is 34.79. The increased Si/Ti ratios of TS‐1‐m and s‐TS‐1‐m(0.3) indicated that the extraframework Ti species can be washed away by muriatic acid, which agrees with the UV/vis spectra (Figure C).…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation